Residência Pedagógica em tempos pandêmico: o ensinar através das tecnologias e mídias digitais - Santos, Mayelle Brito dos (Universidade Federal do Tocantins, 2023)
This study consists of field reports of activities developed within the scope of the Pedagogy Residency Program, aiming at remote teaching and its teaching practices with the use of digital media as a pedagogical resource. The research had as methodology, the qualitative approach. The program development process was carried out at the Irmã Lucília Municipal Child Education Center with the support of the regent teacher in the implementation of activities and the preceptor who supported and encouraged pedagogical research in directing activities and in the practice of new teaching methods. The research in its development aims to study the acceleration of the use of digital media in everyday life and especially in the pandemic period, and with that, the possibility of being as an educational resource, highlighting the production of interactive video in the pandemic; contextualizes the importance of school public relations and reports on practices carried out in remote teaching. Some basic theorists of this study are also emphasized: Baggio (2000), Kenski (2007) and (2008), Nóvoa (2022), Moreira (2020), among other authors that make up this discourse. Given the moment of social distancing due to the pandemic, the methodology applied to emergency remote teaching needed to be updated, and also in the family-school relationship, as the search for alternatives and solutions was considered to find ways that could help parents to encourage their children. to participate in activities and daily returns. Therefore, being part of the program at an atypical time provided a great experience in professional growth and identity construction as a teacher. As a result, the activities developed at the ERE, based on research, practice and evaluation, resulted in new methods, in order to contribute to education, evidencing professional autonomy in the teaching and learning process in the construction of being a teacher during graduation.